Utilization of LAZ Alwasliyah Charity (Washal) - Basyarul Ulya (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
The Zakat is an alternative to save communities from poverty, eliminate economic disparities, improve family welfare, and enhance the quality of life. North Sumatra, a large province with abundant natural and human resources, recorded that as of September 2021, 8.49% of its population was still categorized as poor. Bank Indonesia recorded that North Sumatra's economic growth in 2021 had not yet returned to normal and was still lower than the average growth rate of 5.16% for the 2015-2019 period (Bank Indonesia, 2022). LAZ Washal (Lembaga Zakat, Infaq, and Alms) has extensive and promising capacity in collecting and distributing zakat, alms, and donations. However, in reality, the collection of zakat, infaq, and alms from LAZ Washal remains minimal. Furthermore, LAZ Washal has a significant capacity to develop its institution, given its large assets and existing human resource network. The researcher limited this research to the act of examining aspects of LAZ Al Wasliyah Beramal (Washal) in increasing Fundraising in North Sumatra Province with the Penta Helix model. The purpose of this study is to evaluate the utilization of LAZ Alwasliyah Beramal (Washal). The type of research used in this study is inductive qualitative research. The data collection technique uses observation, followed by Pentahelix model interviews by taking 2 people each per field of expertise, namely representatives from the fields of Academics, Business, Government, Media, and Community. collaborated with the SWOT Analysis Method. The results of the study found that based on the data, the amount of potential fundraising LAZ Alwasliyah Beramal (Washal) if managed to reach a maximum of 36.25 billion per year. The results of the SWOT Analysis of LAZ Alwasliyah Beramal (Washal) are in quadrant III with the Turn Around Strategy, namely the priority strategy of LAZ Alwasliyah Beramal (Washal) to conduct a comprehensive evaluation both internally and externally.